Large-vessel giant cell arteritis: diagnosis, monitoring and management. (23rd February 2018) - Koster, Matthew J; Matteson, Eric L; Warrington, Kenneth J
Abstract: GCA is a chronic, idiopathic, granulomatous vasculitis of medium and large arteries. It comprises overlapping phenotypes including classic cranial arteritis and extra-cranial GCA, otherwise termed large-vessel GCA (LV-GCA). Vascular complications associated with LV-GCA may be due, in part, to delayed diagnosis, highlighting the importance of early identification and prompt initiation of effective therapy. Advancements in imaging techniques, including magnetic resonance angiography, CT angiography, PET and colour duplex ultrasonography, have led to improvements in the diagnosis of LV-GCA; however, the role imaging modalities play in the assessment of disease activity and long-term outcomes remains unclear. Glucocorticoids are the mainstay of therapy in LV-GCA, but their prolonged use is associated with multiple, sometimes serious, adverse effects. Recent data suggest that biologic therapies, such as tocilizumab, may be effective and safe steroid-sparing options for patients with GCA. However, data specifically evaluating the management of LV-GCA are limited.